Assessment of Stigma among Caregivers of Armed Forces Professionals Suffering from Mental Illness - Chandrima Bhattacharya; Sanjay Kumar; Alok Kumar Sinha; Parvaiz Ahmad; Shafiq Ahmad; Harpreet Singh; Aijaz Ahmad (Journal of Marine Medical Society, 2025)
Background: Having a person with mental illness in the family invariably leads to stigmatic experiences to the family members. Perceived stigma in caregivers leads to social isolation, psychological distress, and suboptimal functioning. Additionally, perceived stigma among such caregivers is one of the barriers that prevent them from taking appropriate care of their dependents with mental illness. There has been little research in this field in the Indian armed forces population. Objective: The objective of this study was to assess the perceived stigma among caregivers of armed forces personnel suffering from mental illnesses. Methods: The calculated sample size was 139 but in our study period of time (December 1, 2019–February 28, 2020) we received the enough number of patients and we continued our study with 150 study subjects which is enough more than the 139. Hence, the total number of 150 caregivers visiting the psychiatry outpatient department of a tertiary care military hospital in North India along with their mentally ill dependents were included in the study after obtaining valid informed consent. The subjects were interviewed, their sociodemographic data were collected, and stigma scores were assessed on a 15-item Explanatory Model Interview Catalogue (EMIC) Stigma Scale. Results: Total stigma score ranged from 20 to 40 with a median of 31. Caregivers with lower level of education, lower income, rural residency, elder age, and diagnosis of psychosis/substance abuse in dependent were found to have higher scores of perceived stigma. Conclusions: Caregivers of patients with mental illnesses experience significant stigma which needs to be addressed so that they can provide optimum care to their mentally ill dependents. Limitation: As EMIC does not provide any standard cutoff for low or high stigma or to categorize persons as having stigma or not, it was difficult to compare results with other studies that used different tools to assess stigma.